Local Specialty Food as Tourism Potential - KP Dalem, Anak Agung Gede Putra (Gastronomy Tourism Journal, 2021)
Food is one of the cultures of a region that can be enhanced to become a tourist attraction. However, due to a lack of community understanding, they are unable to understand this potential, so there is no data for conservation, and they continue to allow young people to be carried away by the flow of modernization, particularly in the introduction of local specialties. On the other hand, the trend of tourists visiting on tourist destination is due to its unique local food that cannot be found anywhere else. For this reason, tourism supporters that must be visited and cannot be brought home are the local specialties of an area that is a tourist visit area, in addition to the loss of identity and one of the assets that can be used as a tourist attraction.Â